2022
DOI: 10.1016/j.arthro.2021.07.030
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic Acid Use in Anterior Cruciate Ligament Reconstruction Decreases Bleeding Complications: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…As a countermeasure for postoperative bleeding, tranexamic acid (TXA) administration plays a key role in various surgical fields [11,12]. In recent years, a number of randomized controlled studies have revealed the effectiveness of TXA in reducing perioperative blood loss in patients undergoing total joint arthroplasty [13,14], and a consensus has been reached regarding its efficacy in this patient population.…”
Section: Introductionmentioning
confidence: 99%
“…As a countermeasure for postoperative bleeding, tranexamic acid (TXA) administration plays a key role in various surgical fields [11,12]. In recent years, a number of randomized controlled studies have revealed the effectiveness of TXA in reducing perioperative blood loss in patients undergoing total joint arthroplasty [13,14], and a consensus has been reached regarding its efficacy in this patient population.…”
Section: Introductionmentioning
confidence: 99%
“…As a countermeasure for postoperative bleeding, tranexamic acid (TXA) administration plays a key role in various surgical elds [11,12]. In recent years, a number of randomized controlled studies have revealed the effectiveness of TXA in reducing perioperative blood loss in patients undergoing total joint arthroplasty [13,14], and a consensus has been reached regarding its e cacy in this patient population.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of them only focused on its antifibrinolytic effects on short-term outcomes—including hemarthrosis and drain output. 2,29 Currently, a randomized controlled trial (NCT03552705) is investigating the effect of systemic TXA treatment during ACLR surgery on acute joint inflammation and long-term cartilage health in patients with ACL ruptures.…”
mentioning
confidence: 99%